(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2026)
Background: Insertional Achilles tendinopathy is a prevalent overuse disorder that often persists despite traditional interventions like rest, orthoses, and exercise therapy. When conservative measures fail, extracorporeal shockwave therapy (ESWT) serves as a promising non-invasive alternative. This study evaluated the effectiveness of low-energy ESWT for chronic insertional Achilles tendinopathy in a local hospital-based population. Methods: This quasi-experimental study was conducted at Chittagong Medical College Hospital from October 2021 to April 2022. The study enrolled 39 adults with chronic symptoms lasting at least 3 months, a morning pain visual analogue scale (VAS) score above 5, and a history of failed conservative treatment. Participants received four weekly ESWT sessions; corticosteroids were prohibited. Outcomes were measured using the VAS for pain and the Roles and Maudsley score (RMS) for functional status, with follow-ups at 1, 2, and 3 months post-treatment. Data were analysed using repeated-measures ANOVA with Bonferroni-adjusted post hoc comparisons. Results: The mean baseline VAS score was 7.9 (0.8), decreased to 4.6 (0.7) at 1 month and 2.3 (0.5) at 3 months (P <0.001). The mean RMS improved from 2.9 (0.7) at baseline to 0.9 (0.6) at 3 months (P <0.001). Post hoc analysis showed significant improvement from baseline to each follow-up for both outcomes; for VAS, all pairwise comparisons remained significant, whereas for RMS the difference between 2 and 3 months was not significant after adjustment. Conclusion: Low-energy ESWT provides substantial short-term pain relief and functional recovery for patients with recalcitrant insertional Achilles tendinopathy.